THE EFFECT OF TEACHING STRATEGIES AND STUDENTS’ PERSONALITIES ON STUDENTS’ ACHIEVEMENT IN WRITING - Sri Dewi Yanti; Anni Holila Pulungan; I Wayan Dirgeyasa (Universitas Negeri Medan, 2020)
The objectives of this experimental research were to investigate whether 1) students’ achievement in writing taught by using Two Stay Two Stray teaching strategy was higher than taught by using Think Talk Write teaching strategy, 2) students’ achievement in writing with extrovert personalities was higher than those with introvert personalities, 3) there was interaction between teaching strategies and students’ personalities on students’ achievement in writing. The population of this research was the students in Grade X of Setia Budi Abadi Senior High School students in the 2018/2019 academic years that is located on Jl.Serdang No. 157 Perbaungan. The total number of population was 129 students. There were 64 students selected as sample of this research by applying random sampling. The research design was experimental research by using factorial design 2x2. The students were divided into two experimental groups. The experimental group I was treated by using think talk write teaching strategy and experimental group II Keywords: Think Talk Write Teaching Strategy, Two Stay Two Stray Teaching Strategy, Extrovert, and Introvert.